2014
DOI: 10.1097/iae.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Features of Focal Choroidal Excavation on Spectral Domain Optical Coherence Tomography With Simultaneous Angiography

Abstract: Morphologically, FCE lesions were classified into cone-shaped, bowl-shaped, and mixed types, based on optical coherence tomography findings. Focal choroidal excavation formation may be associated in part with chorioretinal diseases such as age-related macular degeneration and central serous chorioretinopathy, whereas some eyes are considered to have idiopathic FCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 14 publications
6
47
1
3
Order By: Relevance
“…[3][4][5][6][7] In our study, the prevalence of FCE in CSC patients was found to be 6.0%, which was slightly lower compared with the prevalence of 7.8% reported by Ellabban et al 4 in 116 eyes with CSC. However, our rate was higher than the prevalence of 2.8% reported by Suzuki et al 6 in another Japanese study of 248 eyes with CSC.…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…[3][4][5][6][7] In our study, the prevalence of FCE in CSC patients was found to be 6.0%, which was slightly lower compared with the prevalence of 7.8% reported by Ellabban et al 4 in 116 eyes with CSC. However, our rate was higher than the prevalence of 2.8% reported by Suzuki et al 6 in another Japanese study of 248 eyes with CSC.…”
Section: Discussioncontrasting
confidence: 46%
“…This rate was higher compared with previous studies in which 0-24% of patients had FCE bilaterally. [3][4][5][6][7][8][9] The natural course of FCE remains unclear as most of the published studies were cross-sectional studies. There were only a few studies with longitudinal follow-up data available and the majority of the excavations appeared to remain stable with follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations